Understanding Independence: Board of Directors and CSR - Calderón, Reyes; Piñero, Ricardo; Redín, Dulce M. (Frontiers in Psychology, 2020)
On August 2019, the Business Roundtable redefined the purpose and social responsibility of the corporation. Yet, this statement must be followed by substantial changes in the business models of corporations for it to avoid becoming empty rhetoric. We believe that the figure of the independent director may be one of the catalysts needed for this change of paradigm for corporations. In spite of the positive correlation between Corporate Social Responsibility (CSR) and board independence, the development of the independence of boards during the last decade has not lead to the expected CSR results. Academics and regulators point to a weak definition and the non-standardised measurement of both independence and board independence (BI) as one possible explanation, and agree that a broader definition is needed. This paper aims to contribute to this debate. We develop a second-generation definition of independence based on a positive approximation to the concept by integrating an Aristotelian perspective of virtue ethics with the best practices of corporate governance. Thus, we define independence as a virtue guided by practical wisdom, that implies autonomy and autarky and which enables a person to act with integrity, fairness and truthfulness. In the context of corporate governance, independence is associated with an honest disposition to serve. Our proposal has political implications for supervisors that make decisions relating to the suitability of board members.